Effect of Glyceryl Monoolein Addition on the Foaming Properties and Stability of Whipped Oleogels - Eleftherios G. Andriotis; Paraskevi-Kyriaki Monou; George Komis; Nikolaos Bouropoulos; Christos Ritzoulis; Georgios Delis; Evangelos Kiosis; Georgios Arsenos; Dimitrios G. Fatouros (Gels, 2022)
Medium Chain Triglyceride (MCT) oil was successfully combined with Glyceryl Monostearate (GMS) and Glyceryl Monoolein (GMO) to form oleogels that were subsequently whipped to form stable oleofoams. The co-crystallization of GMS and GMO at a ratio of 20:1, 20:2.5, and 20:5 within MCT oil was studied through Differential Scanning Calorimetry (DSC), X-ray Diffraction analysis (XRD), rheological analysis, Fluorescence Recovery after Photobleaching (FRAP), Fourier Transform Infrared Spectroscopy (FTIR), and polarized microscopy. The addition of 5% GMO resulted in the production of more stable oleogels in terms of crystal structure and higher peak melting point, rendering this formulation suitable for pharmaceutical applications that are intended to be used internally and those that require stability at temperatures close to 40 °C. All formulations were whipped to form oleofoams that were evaluated for their storage stability for prolonged period at different temperatures. The results show that oleofoams containing 5% MGO retained their foam characteristics even after 3 months of storage under different temperature conditions.